Deteksi Gen Penyandi Sifat Resistensi Metisilin, Penisilin dan Tetrasiklin pada Isolat Staphylococcus aureus Asal Susu Mastitis Subklinis Sapi Perah - Fatkhanuddin Aziz; Fajar Budi Lestari; Sarah Nuraidah; Endah Purwati; Siti Isrina Oktavia Salasia (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Detection of gene encoding resistance of bacteria could be used as an accurate method to determine resistance of Staphylococcus aureus which is causing mastitis in dairy cows to the several antibiotics. This research aimed to detect the gene encoding resistance of methicillin, penicillin and tetracycline from identified S. aureus. Sixty milk samples were collected from subclinical mastitis of cows from various dairy farming in Yogyakarta. Isolation and identification of S. aureus based on the culture, Gram staining and biochemical test. Phenotypes of S. aureus resistances against antibiotics were carried out by disc diffusion method, meanwhilespecies specific gene of S. aureus and the gene encoding methicillin, penicillin and tetracycline were confirmed by PCR method. The results showed 11 isolates representing of Methicillin Susceptible Staphylococcus aureus (MSSA) could be identified, wherein 5 isolates were harboring both of penicillin and tetracycline resistant genes respectively.